The ’secret’ to student success – factors influencing achievement in music education and training - Милић, Тијана (Norma, 2025)
Summary: Musical achievement as a general goal of music education and upbringing is a complex product of long-term growth and development of artists, influenced by numerous factors, which is also a challenging topic for research. The topic requires a holistic research approach that will provide us with possible paths and potential factors that influence musical development. Our research is focused on examining the attitudes of teachers and students in order to discover possible solutions that contribute to achieving musical success, in our case, participation or success in music competitions, as one of the possible indicators. The research was conducted during the 2022/23. school year on a sample of 123 participants: 66 teachers and 57 students. Through the analysis of research results, factors that were highly valued by both students and teachers in terms of their significance were identified (M > 4.50): 1) personal contribution of students (teacher’s perspective: M = 4.84; student’s perspective: M = 4.59); 2) teacher influence (teacher’s perspective from the students’ point of view: M = 4.80; student’s perspective: M = 4.52); 3) love for music (student’s perspective: M = 4.63); 4) parental influence (teacher’s perspective: M = 4.51). By applying parametric techniques for group comparison, we determined that students from the Elementary Music School value teacher influence, parental influence, and personal contribution as factors for achievement more than students from the SMS at a significance level of p<0.05. This indicates that they expect a stimulating environment and support during their elementary music education. Research on this topic requires constant examination and evaluation in order to expand knowledge and improve practice. We must also not overlook the benefits of music education, which may not necessarily result in success and external outcomes. We aim to highlight the educational aspect of the overall development of students attending music school. Keywords: music education, music achievement, developmental factors, music teachers